The Poetics of Ruins in Renaissance Literature - Hui, Andrew, 1980- (Verbal arts--studies in poetics., 2016)
The Renaissance was the Ruin-naissance, the birth of the ruin as a distinct category of cultural discourse, one that inspired voluminous poetic production. For humanists, the ruin became the material sign that marked the rupture between themselves and classical antiquity. In the first full-length book to document this cultural phenomenon, Andrew Hui explains how the invention of the ruin propelled poets into creating works that were self-aware of their absorption of the past as well as their own survival in the future.